Delay in surgery, risk of hospital-treated infections and the prognostic impact of comorbidity in hip fracture patients. A Danish nationwide cohort study, 2005–2016 - Glassou, Eva N (Clin Epidemiol, 2019)
Purpose: We examined the association between delay in surgery and hospital-treated infections in hip fracture patients with and without known comorbidities. Patients and methods: All hip fracture patients aged ≥65 years registered in the Danish Multidisciplinary Hip Fracture Registry from 2005 to 2016 were included (n=72,520). Delay in surgery was defined as the time in hours from admission to surgery and was divided into 3 groups (12, 24 and 48 hrs). The outcomes were hospital-treated pneumonia, urinary tract infection and reoperation due to infection 0–30 days after surgery. As a measure of comorbidity, we used the Charlson Comorbidity Index (CCI): none (no registered comorbidities prior to the fracture), medium (1–2 points) and high (≥3 points). Results: Overall, there was an association between a delay of 12 hrs and pneumonia. A delay of 12 hrs was associated with an increased risk of pneumonia in patients with no comorbidities (adjusted hazard ratio (HR) 1.20, confidence interval (CI) 1.03–1.40) and a delay of 24 hrs was associated with an increased risk of pneumonia in patients with a medium level of comorbidity (HR 1.12, CI (1.02–1.23)). Overall, delay was associated with reoperation due to infection, particularly among patients with comorbidities, although the confidence intervals of some of the estimates were wide. A delay of 48 hrs was associated with an increased risk of reoperation due to infection in patients with a high level of comorbidity (HR 2.36, CI 1.19–4.69). Conclusion: Delay in surgery was associated with an increased risk of hospital-treated pneumonia and reoperations due to infection within 30 days of surgery. The number of postoperative hospital-treated infections within 30 days may be reduced by continuously targeting pre-, per- and postoperative optimization not only for patients with high level of comorbidity but also for hip fracture patients without known comorbidities prior to surgery.